Blockchain for Patient and HCP Data Rights Management: Lessons from an Enterprise Install - Hurley, Dominique (Blockchain in Healthcare Today, 2018)
Session Description: Privacy laws like GDPR and California Consumer Privacy Act (CCPA) have created a much more regulated environment in which enterprises need to operate in regards to consumer data permissions. Built on hyperledger fabric, HealthVerity Consent is an enterprise-level platform that allows organizations to aggregate and manage all existing touchpoints across the organization in one central location to comply with evolving privacy requirements. In this session we'll review what it took to deliver an enterprise blockchain installation where we drove business process change across departments and companies to better manage rights to data access and use. We’ll cover: 5 key lessons learned you can apply to future blockchain implementations How to integrate into a non-blockchain ecosystem What challenges were faced in order to drive business process change with blockchain How to manage existing barriers when migrating from legacy systems and business process to distributed ledger technology